The effect of sintering temperature on wear resistance of alloys produced by using hot isostatic pressing method - Yildiz, Tulay; Aba, Suleyman (Scientific and Technological Corporation, 2018)
Properties of the new material obtained by hot isostatic pressing with the addition of certain concentrations of cobalt and nickel to the bronze alloy CuSn (85/15). The influence of Co and Ni elements on the wear resistance of the obtained elements was studied. It is shown that when the sintering temperature increases, the samples are more homogeneous. With increasing Co concentration and sintering temperature, the wear resistance of the samples increases. © 2019, Scientific and Technological Corporation.
Keywords: Abrasive wear; HIP (Hot Isostatic Pressing); Microhardness; Powder metallurgy